What Transparency Can Do When Incentives Fail : An Analysis of Rent Capture - Paul, Elisabeth (IMF Working Papers; Working Paper ;, 2006)
This paper analyzes the pervasiveness and persistence of rent seeking, misgovernance, and public sector inefficiency in many developing and transition economies. We formalize evidence from country experiences and empirical studies into a stylized analytical framework that reflects realistic constraints faced in these countries. Our work departs from the standard economic literature by assuming that (i) the relationship between the government and its population is regulated through an implicit social consensus; (ii) traditional incentives (in the form of public expenditure controls, sanctions, or monetary incentives to perform) are, for various reasons, ineffective in many of these countries; and (iii) the persistence of high corruption reflects a very stable equilibrium, which in turn reflects the fact that several constraints are simultaneously binding. We argue that, when traditional incentives fail, transparency-information provision and disclosure, together with the means to use it-by relaxing different constraints, can contribute to improving public outcomes.